Promoting a Teacher Education Research-Oriented Curriculum for Initial Teacher Training in English as a Foreign Language - Ceia, Carlos (2017)
Research-oriented programs related to pre-service teacher education are practically non-existent in many countries. Since in Portugal we now have a stable legal system for initial teacher training, how can we help these countries to respond to their teacher training needs and accomplish these same standards? How can we create an international program at MA level that could serve such an objective? What are the research priorities for teachers in primary and secondary education? I will claim for a new general research policy using small-scale research projects in foreign language teaching (FLT), which illustrated a turning point in advanced research in foreign languages teacher training. Presently, researchers no longer narrow their inquiries into linguistic questions or school and student-centered actions. Instead, they focus on a range of issues such as teacher-centered actions, beliefs and policies, and aspects of FLT such as literacy education, special educational needs or methods for teaching gifted students. Despite a lack of funding at all levels, many research projects in teacher education have been undertaken, and new areas have been explored, such as didactic transposition, literary and information literacies, intercultural learning, corpora in FLT, new information and communication technologies in FLT, interlingual inferencing, national standards for foreign language education, FLT for specific purposes, digital narratives in education, CLIL, assessment, and language learning behaviors. This small sample of the many areas covered proves that advanced research in teacher education can also be very useful to promote the growing interest in further internationalization in other sciences (beyond human and social areas) traditionally linked to politics, business and industry (computing, chemistry, biology, medicine, etc.), something that can only be attained by focusing on multilingualism, multi-literacy and lifelong learning.